Menata SMPN 01 Pulau Pari Menuju Sekolah Peduli dan Berbudaya Lingkungan (Adiwiyata) - Jasin, Faisal M.; Anwar, Haerul; Agustina, Dwi; Kamila, Nisaul; Akmal, Ali; Purwanto, Anim (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Climate change, environmental pollution, and ecological crisis are global issues that require early attention. Schools have a strategic role in instilling environmental awareness and culture in the younger generation. This community service supports sustainable education efforts through the application of environmental care values ​​and culture at SMP Negreri 01 Pulau Pari. Community service is carried out through socialization, training, and mentoring in the application of the Adiwiyata principles. All activities are monitored and documented to support the sustainability of the program. The results show that this community service activity has been carefully designed and implemented very well, so that it runs on time according to the schedule that has been set. The material presented is very relevant to the needs of the participants, so that it provides direct benefits and is in accordance with expectations. The facilities provided are complete and support the smooth running of the activity, while the committee's service is very satisfying and responsive to the needs of the participants. In addition, the facilitators involved are considered quite effective and communicative in delivering the material, able to explain clearly and build good interactions with participants, so that the learning atmosphere becomes more lively and interactive. Community service activities have provided applicable knowledge and insight for the school environment, strengthened the relationship between schools and universities, and enriched the experience and motivation of the community.